Experience of managing acute pancreatitis in a surgical unit of a tertiary care hospital - HaroonurRashid,IhtashamMuhammadCh,AhmadRaza,MuhammadAsghar,HamidRasheedGoreja,SabaMaqsood, HaroonurRashid,IhtashamMuhammadCh,AhmadRaza,MuhammadAsghar,HamidRasheedGoreja,SabaMaqsood (Journal of Rawalpindi Medical College, 2019)
Objective: To study the etiology, diagnosis, treatment and complications of acute pancreatitis in a tertiary care hospital. Methodology: Study Design: It was a descriptive study. The study was conducted at Surgical Unit of Benazir Bhutto Hospital (BBH) Rawalpindi from 1st January 2014 to 31 July 2017. All the patients who presented in emergency with abdominal symptoms and diagnosed as a case of acute pancreatitis were included in the study. All the data of gender, age, serum amylase & lipase, etiology, CT severity index, Ranson’s criteria, complications, mortality and management were noted on a predesigned proforma. Percentages and frequencies were calculated for all the data by SPSS 21 version. Results: Total 161 patients were included in the study, with 60.9% females and 39.1% males. Maximum patients 31% were from age group of 26 to 40 years of age and minimum 1.2% from 71 to 85 years. Gall stones were the major cause of the disease contributing 67% of cases. At admission Ranson’s score of the maximum patients 32.2% had total score of 1, While only 1.2% had moderate pancreatitis. After 48 hours of admission 24.2% had 2 score while only 1.2%had severe pancreatitis. The radiological CT severity index 82.6% patients had mild pancreatitis while1.2% patients had severe disease. 93.1% patients were managed conservatively, 1.9% patients went Cystogastrostomy, 1.2% patients needed Exploratory laparotomy and 1.2% patients went for Pancreatic Necrosectomy. On calculating the morbidity 67.7% patients had no significant morbidity. 32.3% had complications including pleural effusion, ascites, pancreatic necrosis, pseudo cyst formation, shock, acute renal failure and multi organ failure. Overall mortality rate was 3.7%. Conclusion: Acute pancreatitis in our set up is mainly due to gall stones. A multidisciplinary approach, measurement of severity of disease with computerized tomography scan and Ranson’s scoring system is always helpful in disease management and its complications. Key Words : Acute pancreatitis, Gall stones, Ranson’s scoring, Pancreatic necrosis, Pseudocyst.